Investigating the interrelationships among food habits, sports nutrition knowledge, and perceived barriers to healthy eating: a study of adolescent swimmers - AlKasasbeh, Walaa; Akroush, Sofia (Frontiers in Nutrition, 2024)
This cross-sectional study investigates the complex interrelationships among food habits (FH), perceived barriers to healthy eating (PBHE), and sports nutrition knowledge (SNK) in a cohort of 52 adolescent swimmers aged 12 to 18 from Al Hussein Youth Club in Al-Hussein Sport City. Utilizing Pearson Correlation analysis, a significant positive association between FH and SNK was revealed (r = 0.393, p = 0.004). Moreover, stepwise regression analysis identified Knowledge as a positive predictor of food habits (β = 0.393, p = 0.004), underscoring the influential role of sports nutrition knowledge in shaping the dietary choices of adolescent swimmers. The introduction of Barriers lacked significance, and individual predictors did not reach statistical significance. These findings underscore the need for targeted interventions aimed at enhancing nutritional education among adolescent swimmers. The study provides valuable insights into the multifaceted dynamics that shape the dietary choices of young athletes, emphasizing the interplay between knowledge, barriers, and overall food habits.